1999
DOI: 10.1148/radiology.213.2.r99nv32561
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of the Amplatz Thrombectomy Device with Modified Pulse-Spray Pharmacomechanical Thrombolysis in the Treatment of Thrombosed Hemodialysis Access Grafts

Abstract: The ATD and modified PPT were similarly successful in the recanalization of thrombosed hemodialysis access grafts and achieved comparable primary patency rates. The higher rate of local complications and technical difficulties encountered with use of the 8-F ATD limit its usefulness for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 22 publications
2
16
1
1
Order By: Relevance
“…However, owing to follow-up limitations in the study period, we only had 1-and 3-month data available at the time of writing. Our 1-and 3-month primary patency rates of 81.1% and 63.6% are comparable to previous published studies (18)(19)(20)(21).…”
Section: Procedural Resultssupporting
confidence: 91%
“…However, owing to follow-up limitations in the study period, we only had 1-and 3-month data available at the time of writing. Our 1-and 3-month primary patency rates of 81.1% and 63.6% are comparable to previous published studies (18)(19)(20)(21).…”
Section: Procedural Resultssupporting
confidence: 91%
“…In the current series an arterial embolus was diagnosed in 0.38% of the cases; the percentage of these that were symptomatic was not recorded. Table 3 compares the complications that have been reported in the literature [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] with those seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that most complications encountered during percutaneous thrombolysis or surgical thrombectomy of thrombosed prosthetic access could be treated at the same sitting, allowing the same access to be used for hemodialysis. 114 Percutaneous excimer laser-facilitated thrombus vaporization is also found to be safe and effective for recanalization of acute and subacute thrombotic occlusions of hemodialysis shunts. 115 1.…”
Section: Poor Venous Outflowmentioning
confidence: 99%